2015
DOI: 10.3897/zookeys.523.6114
|View full text |Cite
|
Sign up to set email alerts
|

Seven new hypselostomatid species from China, including some of the world’s smallest land snails (Gastropoda, Pulmonata, Orthurethra)

Abstract: Seven new species of Hypselostomatidae are described from the Chinese province Guangxi: Angustopila dominikae Páll-Gergely & Hunyadi, sp. n., Angustopila fabella Páll-Gergely & Hunyadi, sp. n., Angustopila subelevata Páll-Gergely & Hunyadi, sp. n., Angustopila szekeresi Páll-Gergely & Hunyadi, sp. n., Hypselostoma socialis Páll-Gergely & Hunyadi, sp. n., Hypselostoma lacrima Páll-Gergely & Hunyadi, sp. n. and Krobylos sinensis Páll-Gergely & Hunyadi, sp. n. The latter species is reported from three localities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…The material examined here has spiral threads on the umbilicus and at the base of the shell in sync with Páll-Gergely et al (2015). Panha and Burch (2005) did not observe this characteristic in their investigations of the most similar Thai species Angustopila elevata (Thompson et Upatham, 1997).…”
Section: Angustopila Subelevatamentioning
confidence: 63%
See 3 more Smart Citations
“…The material examined here has spiral threads on the umbilicus and at the base of the shell in sync with Páll-Gergely et al (2015). Panha and Burch (2005) did not observe this characteristic in their investigations of the most similar Thai species Angustopila elevata (Thompson et Upatham, 1997).…”
Section: Angustopila Subelevatamentioning
confidence: 63%
“…Distribution: Tonkinospira species are known from Northern Vietnam so far (Páll-Gergely et al 2015 and this study). Diagnosis: Small conical shell with convex whorls, less than 1.95 mm broad; aperture edentate.…”
Section: Angustopila Subelevatamentioning
confidence: 71%
See 2 more Smart Citations
“…No material of this species was found, and only the type specimen was examined. Páll-Gergely et al (2015c: 31, 55) noted that this species shows a protruding last whorl, narrow umbilicus and simple apertural lip, and suggested that this species should be placed into the genus Krobylos . For the current interpretation of Pa Hia, see Páll-Gergely et al (2016: 13).…”
Section: Resultsmentioning
confidence: 99%